Peran Akuntansi Manajemen dalam Meningkatkan Efektivitas Tata Kelola Perusahaan di PT Ace Hardware Indonesia Tbk. - Azzahra Annisa Rahman; Adhelya Christina Martha Diredja; Siti Syilva Fadia; Chika Lutvita Dewi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study focuses on evaluating the contribution of management accounting to improving efficiency within the corporate governance framework at PT Ace Hardware Indonesia Tbk. As one of the leading companies in the household goods retail sector, PT Ace Hardware is required to consistently apply the principles of good corporate governance in a sustainable, accountable, and transparent manner. Management accounting plays a vital role by providing accurate, relevant, and reliable financial and non-financial information to support managerial functions such as planning, controlling, and decision-making. Through effective cost reporting, budgeting, and performance evaluation, management accounting contributes significantly to strengthening operational efficiency and organizational competitiveness. The methodological approach adopted in this study is a literature review, involving the analysis of various academic references, corporate documents, and governance-related publications. The results show that optimal utilization of management accounting can enhance strategic decision-making, improve operational performance, and reinforce accountability and transparency within the company’s governance structure, supporting sustainable business growth.